White masculinity and the radical right in Europe: an intersectional analytical framework - Guildea, Anna (Frontiers in Sociology, 2025)
This paper develops an intersectional analytical framework to examine the radical right in Europe, focusing on how white masculinity shapes the identity, ideology, and power relations of the party family and its support. Concepts pertaining to privilege, status threat, and appeals to victimhood thread these analytical levels together, linking the micro-functional behaviours and attitudes of men to more macro-sociological concepts such as hegemonic masculinity and the relationship between masculinity, technology, and capitalism. Building on “superordinate intersectionality,” this paper interrogates several overstretched concepts prevalent in radical right scholarship and critiques the discipline's persistent blind spots, particularly its failure to adequately theorise race and gender. By foregrounding white masculinity in its conceptual and analytical endeavour, this paper offers new frames for understanding the radical right.